Time of Occurrence and Age Distribution of Digestive Tract Cancers in Northern Iran - M Mohebbi; K Nourijelyani; M Mahmoudi; K Mohammad; H Zeraati; A Fotouhi; B Moghadaszadeh (Tehran University of Medical Sciences, 2008)
Background: Previous studies indicate a high incidence of digestive cancers along southern parts of Caspian Sea including Mazandaran Province. The present study was conducted to further investigate time to occurrence, age distribution and possible risks associated with the incidence time of digestive cancers in the above regions. Methods: For this purpose the data of digestive cancer incidence of 3723 cases during a five-year period of 2001 to 2005 collected from Babol Cancer Registry Center in Iran. Almost all cancer cases residence of Mazandaran Province is included in this study and so the results could be considered a population-based conclusion. In order to modify the mortality due to other causes before digestive cancers, and to adjust the effect of digestive cancers correlations, a competing risks model was used. The Cox regression model was used for study of risk factors on cancer incidence. Results: Although incidence of colorectal cancer was relatively low, however, unfortunately the age of onset was at the age category of 15-19, much sooner than occurrence of stomach cancer which was at 20-24 yr (P< 0.0001), and esophageal cancer at age category of 30-34 yr (P< 0.0001). Conclusion: Life tables of all digestive cancer, esophageal cancer, stomach and colorectal cancers were presented in this paper. Risks related to these cancers are significantly higher in men and residences of urban areas than their baseline counterparts. (P< 0.0001) More studies needed to identify risk factors and high risk cases for screening and prevention programs.